Investigating the Dimensionality and Stability of Union Commitment Profiles Over a 10-Year Period: A Latent Transition Analysis - Morin, A.; Gallagher, D.; Meyer, John; Litalien, D.; Clark, P. (Cornell University Press, 2019)
We adopt a person-centered approach to the investigation of the dimensionality of the union commitment construct, capitalizing on a 10-year longitudinal study of 637 union members in their first year of employment measured again one and 10 years later. Our results revealed four distinct profiles of union commitment, presenting a stable structure over time. These profiles demonstrated consistency in commitment level across the three most common union commitment dimensions, thus questioning the necessity of adopting a multidimensional approach. Our results showed that union members became more similar to other members of their profiles over time, and that union commitment became slightly less extreme as union tenure increased. Finally, our results showed that union commitment profiles predicted union participation in accordance with our expectations, and suggested that endorsing positive attitudes toward unions and their instrumentality were a stronger predictor of profile membership than satisfaction with the actions of their own union.